2015
DOI: 10.1007/s00232-015-9802-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Protein Structure, Function, and Dynamics: a Perspective from Experiments and Theory

Abstract: Membrane proteins mediate processes that are fundamental for the flourishing of biological cells. Membrane-embedded transporters move ions and larger solutes across membranes, receptors mediate communication between the cell and its environment and membrane-embedded enzymes catalyze chemical reactions. Understanding these mechanisms of action requires knowledge of how the proteins couple to their fluid, hydrated lipid membrane environment. We present here current studies in computational and experimental membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
127
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 273 publications
(339 reference statements)
1
127
0
Order By: Relevance
“…demonstrated that the 1658 cm −1 peak is related to the unfolded state of proteins37. Recent numerical models have shown that pulsed electric fields can alter the folding of membrane proteins38. The evolution of the amide I band may be directly related to the structural modifications of proteins and especially to their folding state.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the 1658 cm −1 peak is related to the unfolded state of proteins37. Recent numerical models have shown that pulsed electric fields can alter the folding of membrane proteins38. The evolution of the amide I band may be directly related to the structural modifications of proteins and especially to their folding state.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation is a widely used computational tool to explore relationships between structure, dynamics, and function of biomolecules [13-16]. It has been applied to a wide variety of biomolecules, in particular proteins [17-19], nucleic acids [20-22], biomembranes [23-26], glycans [27-29], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the structure and function of integral membrane proteins (IMPs) comes with major challenges due to the hydrophobicity and subsequent instability of IMPs in aqueous conditions. 1 Investigating IMPs while imbedded in native-like membrane environments 2 is a pragmatic approach to more accurately mimic their function in vivo. A number of approaches for sequestering IMPs within biomimetic lipids have advanced in recent years.…”
Section: Introductionmentioning
confidence: 99%